2022
DOI: 10.1021/acs.molpharmaceut.1c00994
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Investigations to Explore the Difference between the Diastereomers [177Lu]Lu-SibuDAB and [177Lu]Lu-RibuDAB toward Prostate Cancer Therapy

Abstract: Lu-Ibu-DAB-PSMA, a radioligand modified with ibuprofen as the albumin binder, showed higher accumulation in PSMA-positive tumors of mice than the clinically used [ 177 Lu]Lu-PSMA-617 but lower retention in non-targeted tissues than previously developed albumin-binding PSMA radioligands. The aim of this study was to investigate whether the stereochemistry of the incorporated ibuprofen affects the radioligand's in vitro and in vivo properties and to select the more favorable radioligand for further development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…The PSMA ligands used in this study were synthesized using solid-phase chemistry methods as previously reported [ 17 , 18 ]. The labeling of the PSMA ligands with actinium-225 was performed at ITM Medical Isotopes GmbH, Munich, Germany ( Supplementary Material: Section S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PSMA ligands used in this study were synthesized using solid-phase chemistry methods as previously reported [ 17 , 18 ]. The labeling of the PSMA ligands with actinium-225 was performed at ITM Medical Isotopes GmbH, Munich, Germany ( Supplementary Material: Section S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the experiment, the molar activity of the radioligands was adjusted by adding unlabeled ligand and the final formulation was prepared by adding vehicle (saline with 0.05% bovine serum albumin (BSA)) to obtain the desired activity concentration. Radiolabeling of SibuDAB with lutetium-177 (5–10 MBq/nmol) was performed as previously reported [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations